Collected essays. Volume IV, Philosophy of law - Finnis, John. (Oxford : Oxford University Press, 2011)
This volume of John Finnis's collected essays shows the full range and power of his contributions to the philosophy of law. The volume collects over 20 papers on the foundations of law's authority; major theories and theorists of law; legal reasoning revolutions, rights and law; and much more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Philosophy